Regional growth in Hungary - The impact of European economic integration - Anna Iara (European Regional Science Association (ERSA), 2005)
At the enlargement of the European Union, the integration of the Central European applicant countries to the European economic area had already been widely implemented. In particular, trade reorientation to the West and foreign direct investment (FDI) had generated intensive economic linkages between old and new EU members. Transformation and economic integration have further resulted in changing patterns of regional specialization. At the same time, the Central European applicant countries experienced considerable regional disparities in economic growth. In Hungary too, sizeable regional disparities opened up in the 1990s. Motivated by recent economic theories this paper looks at the impact of some factors of European economic integration, in particular of FDI density, orientation to foreign markets, and manufacturing specialisation, on regional growth in Hungary at the NUTS III level. With panel data covering the years 1994-2001, I perform growth regressions with OLS, after finding regional fixed effects insignificant. I check for the robustness of the results to the omission of the capital region and to the correction for contemporaneous correlation across regions. I find that the share of agricultural employment and the change in export orientation of the regions are the paramount determinants of regional growth. A region having twice as high a share in agricultural employment than another produces a growth rate that is 15-20% lower. Besides, faster growing regions also have extensive export activity. Doubling the share of export in manufacturing output enhances the growth rate by around 7%. Investment per capita, the change in the employment rate, FDI density and the change in regional specialisation are found to enhance regional growth in some but not all specifications. Since higher growth of the back-lagging regions in Hungary can be expected from onward structural change with labour moving out of the agrarian sector, policies designed to address development issues in rural areas should therefore be an important aspect of regional policy. Promoting the orientation of the Hungarian economic actors towards foreign markets is also likely to be beneficial for the boost of regional growth.
Keywords: 330